Creation of the Formalized Scheme of Chemical Transformations for Pentane, Hexane and Heptane in Case of Their Processing on ZSM-5 Type Zeolite Catalyst; Petroleum and Coal; Vol. 64, iss. 2 - Altynov A. A. Andrey Andreevich; Bogdanov I. A. Ilya Aleksandrovich; Lukjyanov D. M. Daniil Maksimovich; Kirgina M. V. Mariya Vladimirovna (2022, 2022)
Title screen